THE ORNITHOLOGICAL IMAGE-SYMBOL «EAGLE» IN LITERARY AND FOLK POETRY: BRITISH-UKRAINIAN CONTEXT - Karbashevska, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article makes an attempt of the overall analysis of the peculiarities of symbolism of the bird «eagle» in author’s and folk poetry in the context of ethnic cultures of the United Kingdom, the USA and Ukraine, classical and Ukrainian mythology, as well as British history. It traces the continuity of established dominant features of this ornithological image-symbol.